2022
DOI: 10.46690/capi.2022.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling on Gulong shale oil and wettability of reservoir matrix

Abstract: Understanding molecular interactions between oil and reservoir matrix is crucial to develop a productive strategy for enhanced oil recovery. Molecular dynamics simulation has become an important method for analyzing microscopic mechanisms of some static properties and dynamic processes. However, molecular modeling of shale oil and reservoir matrix is still challenging, due to their complex features. Wettability, which is the measurement of oilmatrix interactions, requires in-depth understanding from the micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Inorganic pores and fractures are dominantly significant in the shale oil generation window, and organic pores are significant in the shale gas generation window. Several investigations have been performed on the role of the mineral-hosted pore-fracture network and microscopic mechanism of the liquid hydrocarbon storage in these in lower-thermal-maturity, lacustrine shale. ,, Recently, it has been shown that inorganic minerals can host abundant pore-fracture networks during deposition to burial as overburden stress and diagenesis increase . Loucks et al suggested that rigid mineral particle skeleton support, mechanical compaction, and later dissolution strongly control the inorganic pore-fracture formation and development.…”
Section: Shale Oil Storage Within Lower-thermal-maturity Lacustrine S...mentioning
confidence: 99%
“…Inorganic pores and fractures are dominantly significant in the shale oil generation window, and organic pores are significant in the shale gas generation window. Several investigations have been performed on the role of the mineral-hosted pore-fracture network and microscopic mechanism of the liquid hydrocarbon storage in these in lower-thermal-maturity, lacustrine shale. ,, Recently, it has been shown that inorganic minerals can host abundant pore-fracture networks during deposition to burial as overburden stress and diagenesis increase . Loucks et al suggested that rigid mineral particle skeleton support, mechanical compaction, and later dissolution strongly control the inorganic pore-fracture formation and development.…”
Section: Shale Oil Storage Within Lower-thermal-maturity Lacustrine S...mentioning
confidence: 99%
“…To bridge our understanding of the intricacies of wetting phenomena with the molecular-level nuances, molecular dynamics (MD) simulations have emerged as an indispensable tool. Most MD simulations, nevertheless, have primarily focused on homogeneous and smooth surfaces such as graphene and graphite, , but these do not properly represent kerogen’s heterogeneous and rough nature. , To gain deeper insights into wettability, recent studies have started to employ more realistic models of kerogen in which wettability is described by the wetting contact angle of the fluid on the kerogen surface (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in demand and consumption of light crude oil has led to a decline in global oil reserves and supply. Therefore, short-term and long-term demand needs to be supplemented by unconventional oil resources [1][2][3][4][5][6][7][8]. Heavy oil resources are widely spread around the world.…”
Section: Introductionmentioning
confidence: 99%